On certain class of meromorphic harmonic concave functions defined by Salagean operator - Khalid Callab,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2015)
A class of meromorphic harmonic concave functions defined by Salagean operator in the unit disc is introduced. Coefficient bounds, distortion inequalities, extreme points, geometric convolution, integral convolution and convex combination for the functions belonging to this class have been achieved.